E-Governance and Development Planning: Case Study of Bandung City - Aditya Bagas Pangestu; Adam Koswara; Ariffin Rismansyah; Dzakwan Hasby Yusman; Fadillah Ananda Hermawan; Fahmi Idris (Social Impact Journal, 2024)
E-governance planning plays a crucial role as a strategic step in the modernization of public services. This study uses a descriptive qualitative approach using interviews, observations, and document analysis to examine the development of E-Governance in Bandung City. The findings reveal that e-governance implementation focuses on improving data security, institutional arrangements, and information technology management. The government uses robust physical and software security measures, including security codes and penetration testing, to protect data. The city's SPBE index has improved steadily each year since the implementation of the e-government system. Institutional arrangements have been strengthened through central government legitimacy, clear regulations, and oversight by the Department of Administrative and Bureaucratic Reform (PANRB). Despite these advances, challenges remain, including gaps in digital access, interagency coordination, integrated data management, and low ICT literacy. This study concludes that effective e-governance planning requires increased inter-agency collaboration, integrated data systems, and improved human resource capacity to achieve efficient, transparent, and accountable public services.